Effect of alkyl distribution in pyrazine on pyrazine flavor release in bovine serum albumin solution. Issue 63 (13th November 2019) - Ma, Yun-Jiao; Wu, Jian-Hai; Li, Xiang; Xu, Xian-Bing; Wang, Zhen-Yu; Wu, Chao; Du, Ming; Song, Liang
Abstract : The methyl groups on the pyrazine ring affect the interaction of pyrazines with BSA. The non-covalent interaction between alkyl-pyrazines and BSA was confirmed. Alkyl-pyrazines could induce the polarity and conformation change of BSA. Abstract : The flavor release mechanism related to the interaction of aroma compounds with proteins is still unclear. In this study, the interaction of protein with pyrazine homologues, such as 2-methylpyrazine (MP), 2, 5-dimethylpyrazine (DP), 2, 3, 5-trimethylpyrazine (TRP) and 2, 3, 5, 6-tetramethylpyrazine (TEP), was investigated to elucidate the effect of alkyl distribution in a pyrazine ring on its flavor release in bovine serum albumin (BSA) solution (pH 7.4). The results of SPME-GC-MS indicated that methyl distribution in a pyrazine ring significantly affected its release from BSA solution. The pyrazines released from BSA solution with an increasing order of MP, DP, TRP and TEP. The inhibition mechanism of alkyl-pyrazine release was further elucidated by the interaction between alkyl-pyrazines and BSA using multiple spectroscopic methods. The non-covalent interaction between alkyl-pyrazines and BSA was confirmed as the main interaction force by the value of the bimolecular quenching constant ( K q > 2 × 10 10 L mol −1 s −1 ). A decrease in the hydrophobicity of the microenvironment between the alkyl-pyrazine and BSA was detected by synchronous fluorescence spectra, which revealed that alkyl-pyrazines were mainly bound on the sites of tyrosine and tryptophan in BSA. The UV-vis absorption spectra and circular dichromatic (CD) spectrum revealed that alkyl-pyrazines could induce polarity and conformation change of BSA. The above results indicated that the structure of the flavor homologues can affect their release in food matrices.